"You Think Differently After Playing This Sport": Experiences of Collegiate Goalball Players. Issue 2 (October 2020) - MacDonald, Cathy; Bryan, Rebecca; Lieberman, Lauren J.; Foley, John T.
The inclusion of athletes with and without disabilities in disability sport, known as reverse integration, has received limited attention in the literature. The purpose of this study was to understand players' experiences in collegiate goalball. One-on-one semistructured interviews were conducted with two males (one with visual impairment, one without impairment) and four females (one with visual impairment, three without impairment) who participated in collegiate goalball programs. Interpretative thematic analysis helped uncover the meaning in participants' goalball experiences. Reverse integration was used as a conceptual framework to guide the interpretation of participant experiences. Four main themes were extracted from the data: (a) the disability advantage, (b) the building of team cohesion, (c) the disappearing disability, and (d) enjoyment and pride. Participation in collegiate goalball allowed students to see disability as an asset and question assumptions regarding teammates' abilities. This study highlights the potential value of providing opportunities for people with and without a disability to participate in sport together.